2004
DOI: 10.1097/01.ccm.0000134267.91520.c0
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin during cardiopulmonary resuscitation: A progress report

Abstract: According to new data from the European vasopressin study, we suggest, first, the administration of 1 mg of epinephrine, followed alternately by 40 IU of vasopressin and 1 mg of epinephrine every 3 mins in adult cardiac arrest victims, regardless of the initial electrocardiographic rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Nevertheless, to date, there have only been a small number of randomized controlled trials of VP in humans. Furthermore, whether these data will translate into improved longterm outcome is not known [12]. The most possible adverse effect of VP administration may be coronary vasoconstriction, although this is still controversial [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, to date, there have only been a small number of randomized controlled trials of VP in humans. Furthermore, whether these data will translate into improved longterm outcome is not known [12]. The most possible adverse effect of VP administration may be coronary vasoconstriction, although this is still controversial [12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whether these data will translate into improved longterm outcome is not known [12]. The most possible adverse effect of VP administration may be coronary vasoconstriction, although this is still controversial [12]. There is no doubt that effective treatment of vasodilatory shock is possible if patients possess normal cardiac performance and are maintained by adequate intravascular volume replacement.…”
Section: Discussionmentioning
confidence: 99%
“…12,13) Clinical studies have shown that patients with heart failure have chronically elevated plasma AVP levels, which may contribute to fluid retention. 12,14) Because AVP has adverse effects on heart failure, AVP activity in the myocardium and coronary vasculature may be influenced by an intrinsic cardiac AVP system.…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10) Vasopressin is a potent vasopressor with extended purposes in the treatment of severe trauma, septic shock, cardiac diseases and during cardiopulmonary resuscitation. (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) In addition, a few researchers have found that vasopressin is absorbed well via the mucosa of the airway and alveoli. (23)(24)(25) The combination of a LMA and vasopressin could be a practical management tool in pre-hospital settings.…”
Section: Introductionmentioning
confidence: 99%